Averaged-Value Modeling and Analysis of 96-Pulse Rectifiers for Harmonic Reduction in Aerospace and HVDC Applications - Aghighi, Sakineh (Management Strategies and Engineering Sciences, 2026)
In recent years, the rapid expansion of More Electric Aircraft systems and high-voltage direct current (HVDC) transmission networks has intensified the demand for power converters that can ensure high power quality with minimal harmonic distortion. Among the well-established solutions, multipulse rectifiers have remained attractive due to their inherent ability to mitigate input current harmonics and improve power factor without the need for complex active filters. Within this family, 96-pulse rectifiers, implemented using double-wound Y/ZYZ transformers or autotransformer-based configurations, offer superior performance by producing nearly sinusoidal waveforms and effectively canceling low-order harmonics. This study develops and analyzes nonlinear averaged-value models for three common 96-pulse rectifier topologies to provide a reliable framework for investigating system dynamics and interactions with constant power loads. A unified generic averaged model is first presented and then tailored to series, parallel, and autotransformer-based structures. The equivalent circuits are derived in such a way that the effects of line resistances, transformer leakage inductances, and interphase reactor (IPR) leakage elements are explicitly included. To validate the accuracy of the proposed models, the averaged-value results are compared with detailed circuit-level simulations conducted in Micro-Cap and, for the autotransformer-based configuration, with prototype experimental tests. The comparisons demonstrate that the proposed models accurately capture both the steady-state operating points and the transient dynamic responses, with deviations of less than a few percent relative to detailed simulations, although high-frequency ripple components are naturally excluded due to the averaging process. Furthermore, the models remain accurate under a wide range of operating conditions, including load variations, changes in source amplitude and frequency, and modifications of DC-link filter parameters. Overall, the results confirm that the developed averaged-value models provide a compact yet accurate analytical tool for the design and performance assessment of high-power multipulse rectifiers in aerospace power systems, uninterruptible power supplies (UPS), and HVDC applications where high efficiency, compactness, and superior power quality are essential.